Pattern recognition receptors in annelids - Prochazkova, P; Roubalova, R; Dvorak, J; Navarro Pacheco, N I; Bilej, M (Developmental and comparative immunology, 2020)
The existence of pattern recognition receptors (PRRs) on immune cells was discussed in 1989 by Charles Janeway, Jr., who proposed a general concept of the ability of PRRs to recognize and bind conserved molecular structures of microorganisms known as pathogen-associated molecular patterns (PAMPs). Upon PAMP engagement, PRRs trigger intracellular signaling cascades resulting in the expression of various proinflammatory molecules. These recognition molecules represent an important and efficient innate immunity tool of all organisms. As invertebrates lack the instruments of the adaptive immune system, based on "true" lymphocytes and functional antibodies, the importance of PRRs are even more fundamental. In the present review, the structure, specificity, and expression profiles of PRRs characterized in annelids are discussed, and their role in innate defense is suggested.
Keywords: PAMP struktury; kroužkovci; přirozená imunita; Signal Transduction; Annelida; zvířata; regulace genové exprese; signální transdukce; Gene Expression Regulation; Acute-Phase Proteins; membránové glykoproteiny; transportní proteiny; toll-like receptory; Toll-Like Receptors; receptory rozpoznávající vzory; Membrane Glycoproteins; Immunity, Innate; proteiny akutní fáze; Animals; Carrier Proteins; Receptors, Pattern Recognition; Tissue Distribution; tkáňová distribuce; Pathogen-Associated Molecular Pattern Molecules